TEACHER PROFESSIONAL MOBILITY AS AN INNOVATIVE TREND AND TODAY'S REQUIREMENT - Chervinska, Inna; Prytuliak, Oksana; Melnyk, Nadiya; Vasylyk, Maryna (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to the theoretical and practical aspects of the problem of professional mobility of the teacher, which is considered by the authors as an innovative trend and an urgent requirement of the modern system of higher education. The authors emphasize that professional mobility can be considered as one of the most essential professional features of a teacher, scientist, and researcher. It is noted that the professional mobility of a teacher is based on pedagogical culture and skills and professional competence. Researchers distinguish the following types of mobility: social, professional, academic, intellectual, socio-cultural, cultural, educational and personal. It is pointed out that the driving forces and motivating factors of professional mobility are usually educational reforms, social innovations, the adoption of a new legal framework, educational concepts, revolutions, wars, rapid development of scientific and technical progress, digitalization of the educational process, structural and institutional changes in the education system of the country, region. It is noted that mobility in the pedagogical field is a special quality of personality that is formed in the process of education and upbringing and has a major impact on the professionalism of a future specialist. The authors indicate that professional mobility means the movement of an individual or a professional group in the socio-professional sphere of society, with or without a change in social status. It is also emphasized that the activity of manifestations of professional mobility is influenced by direct professional training and indicators of its quality, the level of qualification obtained. A high level of professional mobility contributes to the optimization of the educational process in the conditions of rapid aging of knowledge, dynamic development and changes in the market of professions, increasing the dependence of an individual's professional career on the level and quality of the obtained education, on the ability to rebuild and adapt according to social transformations. Keywords: mobility, professional mobility, professionalism, education system, innovations.